Pengaruh penggunaan media meme sejarah terhadap hasil belajar siswa pada pelajaran sejarah di SMAN 51 Jakarta - Fikri Pratama Gemilang; Muhammad Fakhruddin; Nurzengky Ibrahim (Universitas Negeri Malang, 2021)
The purpose of this study is to obtain empirical data on whether the use of historical meme learning media affects students' learning outcomes in history subjects at SMAN 51 Jakarta. The research method used is an experimental method with a